An analysis of the mathematical knowledge needed for a course in physics based on the book "Fundamentals of Physics" - U.P.S.E.C. - Sacro, Consuelo P.
Necessary mathematical competencies in learning high school physics were identified in this study. Specifically, this determined the pre-requisite mathematical concepts, principles and skills that must be mastered before successfully learning physics and their implications on the task of teachers teaching physics and mathematics in high shool and the recommendations to improve efficiency in learning high school physics.